Study protocol for the Melbourne Infant Study: BCG for Allergy and Infection Reduction (MIS BAIR), a randomised controlled trial to determine the non-specific effects of neonatal BCG vaccination in a low-mortality setting. Issue 12 (15th December 2019) - Messina, Nicole L; Gardiner, Kaya; Donath, Susan; Flanagan, Katie; Ponsonby, Anne-Louise; Shann, Frank; Robins-Browne, Roy; Freyne, Bridget; Abruzzo, Veronica; Morison, Clare; Cox, Lianne; Germano, Susie; et al.
Abstract : Introduction: BCG vaccination reduces all-cause infant mortality in high-mortality settings by more than can be attributed to protection against tuberculosis. This is proposed to result from non-specific protection against non-vaccine targeted ('off-target') infections. There is also evidence that BCG protects against allergic diseases. Methods and analysis: The Melbourne Infant Study: BCG for Allergy and Infection Reduction is a phase III multicentre, single-blinded, randomised controlled trial. A total of 1438 healthy neonates will be randomised to receive either BCG vaccination or no BCG vaccination in the first 10 days of life. Measures of allergy, eczema, infection and asthma will be obtained from parent-completed questionnaires 3 monthly in the first year and 6 monthly from 1 to 5 years of age, and clinical assessments at 1 and 5 years of age. Biological samples will also be collected for future immunological studies. Analysis primary outcome: The proportion of participants with measures of allergy and infection (atopic sensitisation, eczema, lower respiratory tract infection) at 1 and 5 years of age, and asthma at 5 years of age. Secondary outcomes: (1) the proportion of participants with additional measures of allergy, eczema, asthma and infections; (2) medication use for eczema and asthma; (3) the severity and age of onset of eczema and asthma; (4) the number of episodes of infection; (5) hospitalisations for infections and (6) laboratory measures of immune responses. Ethics and dissemination: This trial has ethical and governance approval from Mercy Health Human Research Ethics Committee (HREC, No. R12-28) and Royal Children's Hospital HREC (No. 33025) with additional governance approval from Barwon Health and St John of God, Geelong, Victoria. Results of this trial will be published in peer-reviewed journals and presented at scientific conferences. Trial registration number: NCT01906853